Hazards of Repeat Pregnancy during Adolescence: A Case-control Study - Galvão, Rafael Bessa de Freitas; Figueira, Camilla Olivares; Borovac-Pinheiro, Anderson; Paulino, Daiane Sofia de Morais; Faria-Schützer, Debora Bicudo; Surita, Fernanda Garanhani (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2018)
Objective To evaluate the social, obstetric and psychological risk factors related to repeat pregnancy in teenagers.Methods A case control study conducted at Centro de Atenção à Saúde Integral da Mulher (Caism, in the Portuguese acronym), in Campinas, Brazil, from 2015 to 2017. Three groups were selected: a case-group of adolescents who had repeat pregnancy and two control-groups, one consisting of adolescents who had delivered at first time and another one of adult women with more than one deliveries. Participants were asked about habits, socio-demographics characteristics, reproductive and obstetric history and assessed psychological issues.Results Ninety women were enrolled, 30 in each study group. Adolescents with repeat pregnancy have lower self-esteem scores and more ineffective contraceptive use. When compared with teens at first delivery, they had less schooling level (odds ratio [OR] 4.03 [1.37–11.8]), more school abandon (OR 8.16 [2.36–28.2]) and drugs use (OR 4.97[1.39–17.8]). Non-white skin color (OR 6.2 [1.15–41.0]), drugs use (OR 17.5 [2.62–116.6]) and first sexual intercourse under 15y (OR 18.0[2.82–115.0]) were found as higher risk factors for repeat pregnancy when comparing adolescents and adults. Moreover, adolescents with more than one gestation had lower self-esteem and greater susceptibility to unplanned pregnancy.Conclusion There was an association between repeat pregnancy among adolescents and lower education, early onset of sexual activity, non-white skin color, low use of contraception and increased use of drugs.
Keywords: adolescence; pregnancy; vulnerability; contraception